2011
DOI: 10.1002/jor.21498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anterior cruciate healing on the uninjured ligament insertion site

Abstract: PURPOSE Changes in the insertion site of the ACL after enhanced suture repair with collagen-platelet-composites (CPC) have not yet been defined. In this study, we hypothesized that fibroblasts and osteoclasts would participate in generating histologic changes in insertion site morphology after transection and bioenhanced repair of the ACL, and that these changes would be age-dependent. METHODS Skeletally immature, adolescent, and adult Yucatan mini-pigs underwent ACL transection and bioenhanced suture repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Adverse effects regarding maximal load, stiffness, and anteroposterior laxity at 90 of flexion also occurred in an agedependent manner. Haus et al 36 showed higher concentrations of reparative cells such as fibroblasts and osteoclasts, as well as blood vessels, in the immature group compared with the mature group in their porcine model. Although it remains to be determined whether these findings occur in humans, it may be an important consideration.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Adverse effects regarding maximal load, stiffness, and anteroposterior laxity at 90 of flexion also occurred in an agedependent manner. Haus et al 36 showed higher concentrations of reparative cells such as fibroblasts and osteoclasts, as well as blood vessels, in the immature group compared with the mature group in their porcine model. Although it remains to be determined whether these findings occur in humans, it may be an important consideration.…”
Section: Discussionmentioning
confidence: 97%
“…Haus et al 36 evaluated the age-dependent cellular response at the insertion site during primary repair of the ACL in a porcine model with 3 different age groups (skeletally immature, adolescent, and adult). Although no significant differences were identified regarding leukocyte counts among any of the age groups, significantly more fibroblastic proliferation, osteoclast activity, and angiogenesis were reported for the skeletally immature and adolescent animals compared with the adult group.…”
Section: Primary Repair Of Aclmentioning
confidence: 99%
“…In studies of reconstructed ACL graft tissue, the highest vascularity was observed between 6–12 weeks [ 43 , 44 ]. In transected ACLs treated with a suture repair plus a collagen-platelet composite sponge, blood vessel concentration at the insertion site was greatly increased at both 2 and 4 weeks in the adolescent injury model [ 45 ]. Thus, the initial inflammatory response may elicit VEGF gene expression and result in increased angiogenesis within the native ligament tissue.…”
Section: Discussionmentioning
confidence: 99%
“…UPA promotes plasmin circulation that leads to fi brin consumption and inhibits formation of a functional clot (Rosc et al ., 2002 ). Due to the lack of a blood clot, the supply of infl ammatory mediators that secrete cytokines and growth factors is diverted towards the synovial fl uid and thus fails to assist in healing of the injured ligament (Haus et al ., 2012 ). It is therefore hypothesized that the lack of functional healing inherent to the ACL may be attributed to the premature loss of the fi brin-platelet provisional clot (Murray et al ., 2006 ).…”
Section: Extra-articular and Intra-articular Ligament Healing Mechanismsmentioning
confidence: 99%